Novel Circulating Tumour Cell-Related Risk Model Indicates Prognosis and Immune Infiltration in Lung Adenocarcinoma - Lu Liang; Yueying Liu; Shiyao Jiang; Jingjing Huang; Hua He; Li Shen; Li Cong; Yiqun Jiang (Journal of Immunology Research)
Background. Lung adenocarcinoma (LUAD) is the most common histological subtype of lung cancer (LC) and one of the leading causes of cancer-related death worldwide. LUAD has a low survival rate owing to tumour invasion and metastasis. Circulating tumour cells (CTCs) are precursors of distant metastasis, which are considered to adopt the characteristics of cancer stem cells (CSCs). Therefore, analysing the risk factors of LUAD from the perspective of CTCs may provide novel insights into the metastatic mechanisms and may help to develop diagnostic and therapeutic strategies. Methods. A total of 447 patients from TCGA dataset were included in the training cohort, and 460 patients from the GEO dataset were included in the validation cohort. A CTC-related-gene risk model was constructed using LASSO penalty–Cox analysis, and its predictive value was further verified. Functional enrichment analysis was performed on differentially expressed genes (DEGs), followed by immune correlation analysis based on the results. In addition, western blot, CCK-8 and colony formation assays were used to validate the biological function of RAB26 in LUAD. Results. A novel in-silico CTC-related-gene risk model, named the CTCR model, was constructed, which successfully divided patients into the high- and low-risk groups. The prognosis of the high-risk group was worse than that of the low-risk group. ROC analysis revealed that the risk model outperformed traditional clinical markers in predicting the prognosis of patients with LUAD. Further study demonstrated that the identified DEGs were significantly enriched in immune-related pathways. The immune score of the low-risk group was higher than that of the high-risk group. In addition, RAB26 was found to promote the proliferation of LUAD. Conclusion. A prognostic risk model based on CTC-related genes was successfully constructed, and the relationship between DEGs and tumour immunity was analysed. In addition, RAB26 was found to promote the proliferation of LUAD cells.